KONDISI PENDIDIKAN KEAGAMAAN PADA KELUARGA MUSLIM DI WILAYAH PERKOTAAN DAN WILAYAH PEDESAAN DALAM PERPEKSTIF ISLAM: STUDI KELUARGA MUSLIM DI KECAMATAN MEDAN DENAI DAN KECAMATAN PANCUR BATU - Syarbaini Saleh (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
The purpose of this study is to obtain valid and accurate information about the state of the implementation of Islamic education in Muslim families in urban and rural areas. The type of research is field research (field research, field work) by observing and searching data directly to the research location and object under study. Sample of urban community study done in District of Medan Denai, Medan City and rural area is done in Pancur Batu Village, Deli Serdang Regency. From the result of the research, it is found that (1) the condition of Muslim family education which is weak and very far from the expectation of Islamic teachings at this time makes the root of the problem of the low quality of Muslims both in urban and rural areas and also become the main factor of powerlessness of education system which exists. (2) The failure of religious education system in the family raises various problems such as moral decadence, high crime rate of drug use and other immorality. (3) There is no significance of Islamic teachings that are perfect with the quantity of the majority Indonesian Muslims. Various efforts to improve the quality of human resources and character education development face the challenge of being powerless due to the weakness of family education